Delayed surgical reconstruction of adult ankle malunion by supramalleolar osteotomy - Opondo, Everisto A. (International Journal of Research in Orthopaedics, 2019)
Background: Malunion of the ankle fractures is a frequent cause of morbidity. The normal ankle is essential for normal mobility. Ankle malunion is a common cause of chronic pain, posttraumatic arthritis and work related disability. The importance of proper treatment of these injuries cannot be over emphasised. Lateral talar shift of only 1 mm decreases the tibio-talar contact area by 42%. This increases contact pressure stress by 36%. Together with instability this results in chronic pain and arthrosis. Methods: A retrospective study was designed to review 21 cases reconstructed after several months to many years of neglect prior to this review. The case reports, operative records, X-rays and CT scans of the patients in addition to physical examination findings were analysed. Results: Good to excellent results were achieved using basic orthopaedic instrument and implants. This technique is an important armamentarium to orthopaedic surgeons in the third world where late presentation of ankle fractures is common and ideal implants are scanty. Conclusions: Good to excellent radiological and functional outcomes are achievable with proper preoperative planning and corrective supramalleolar osteotomies.